A harkányi folyamat, avagy a horvát-magyar határon átnyúló tervezés hajnala - Bali, Lóránt; Hegedűsné Baranyai, Nóra (Közép-Európai Közlemények, 2012)
After the regime change, the Yugoslav civil war significantly slowed the building of official relations of the Croatian-Hungarian border and local municipal. Only after the turn of the millennium was the possibility created for a common design for laying the foundations. On the 25th of August 2000 was the first meeting held, which was followed by later more. The main objective was the preparation for drawing down the resources of the Croatian-Hungarian Pilot Small Projects Fund. The first joint program proved to be successful. The Croatian–Hungarian cross-border cooperation development is highly influenced by the availability of financial resources. Correlating with the deepening of EU’s relations Croatia and our country the amount of available financial tools have increased, offering many new opportunities for the convergence of border areas, as evidenced by the number and diversity of the winning projects. The Hungary-Croatia Pilot Phare Small Projects Fund was characterized by the economic cohesion of the weak border region, the exploration of further cooperation opportunities, and the development of proposals.